2020
DOI: 10.1007/s13595-020-00966-w
|View full text |Cite
|
Sign up to set email alerts
|

CO2 fertilization, transpiration deficit and vegetation period drive the response of mixed broadleaved forests to a changing climate in Wallonia

Abstract: & Key message The change in forest productivity was simulated in six stands in Wallonia (Belgium) following different climate scenarios using a process-based and spatially explicit tree growth model. Simulations revealed a strong and positive impact of the CO 2 fertilization while the negative effect of the transpiration deficit was compensated by longer vegetation periods. The site modulated significantly the forest productivity, mainly through the stand and soil characteristics. & Context Forest net primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Only the optimum response function during chilling (Eq. (1) in de Wergifosse et al, 2020aWergifosse et al, , 2020b was different and had to be adapted to correspond to that given in Duputié et al (2015) (itself based on Wang and Engel, 1998). Leaf yellowing and fall parameters were empirically fitted with the observations provided for 13 of the study sites located in Belgium, Germany, France and Romania.…”
Section: Model Parameterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the optimum response function during chilling (Eq. (1) in de Wergifosse et al, 2020aWergifosse et al, , 2020b was different and had to be adapted to correspond to that given in Duputié et al (2015) (itself based on Wang and Engel, 1998). Leaf yellowing and fall parameters were empirically fitted with the observations provided for 13 of the study sites located in Belgium, Germany, France and Romania.…”
Section: Model Parameterisationmentioning
confidence: 99%
“…The HETEROFOR model has been specifically designed to simulate individual tree growth in structurally complex stands based on a resource-sharing approach and to test the ability of innovative silvicultural systems to improve forest resilience to climate change (de Wergifosse et al, 2020a;Jonard et al, 2020). So far, it has been calibrated and used to simulate the impact of climate change on a couple of forests in Southern Belgium (de Wergifosse et al, 2020b). Yet, one can assume that calibrating a process-based model on a large range of ecological conditions will increase its generality and robustness (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, overall growth trends remained positive regardless of the in-or exclusion of the CO2 fertilization effect (Table 2). In contrast, a similar study in the southern part of Belgium found more moderate growth changes when considering CO2 fertilization and found no significant change in growth when CO2 fertilization effects were excluded (de Wergifosse et al, 2020). The discrepancy between this and our simulation study can probably be partially explained by (i) the different soil conditions, (ii) the wetter climatic conditions in the southern part of Belgium, (iii) the consideration of four sites rather than the 302 sites considered in this study and (iv) the difference in the reference period (1975 -2005 compared to 1961 -1990 for this study).…”
Section: The Effects and Limitations Of Assumptions Underlying The Si...mentioning
confidence: 68%